Experimental Music Patri | Musik Eksperimental Patri - Ida Bagus Putu Da’a Mahadita; Ni Wayan Masyuni Sujayanthi (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Patri musical work raises the idea of creation that was born from the author's empirical experience in playing the reong instrument since studying at SMP Negeri 1 Tampaksiring. This work highlights the processing of the richness of sound color that can be produced by the reong instrument and the writer's creative power as well as the interpretation of contemporary music. The aim is to inspire the public that a single reong instrument can produce a variety of sound colors. The method used in the process of creating a work of patri music is the method of Alma M. Hawkins, which consists of the stages of exploration, improvisation, and forming of the three methods used in the process of creating this work. experimental musical works that use media reveal five types of reong instruments and three types of percussion instruments (panggul) which have different characters. Patri's work uses a tri-angga structure, namely kawitan/prefix (part I), crew/content (part II), pusher/cover (part III), which in each part I and II have three different motifs, while in part III have the same motif with a long meter bar. The creation of this stained music is expected to provide motivation for the younger generation to create works that are not only able to cultivate traditional patterns but who are able develop traditional pattrens